The agglomeration of unrelated high-tech industries : the impact of Jacobian R&D spillovers - Feng, Xueying (2010)
Policy makers have encouraged and established many high-tech industrial zones in China. Recently, there is an increased interest in attracting less related industries to locate near each other, such as the “Optics Valley” in Wuhan East Lake High-Tech Development Zone. The literature so far presents two types of knowledge spillovers that are significant in high-tech industries, commonly known as Marshallian spillovers and Jacobian spillovers. Past studies have shown how R&D spillovers affect the firm’s output level, however they are inconclusive on whether and how it affects firms’ location decision. In our project, a model is build upon the one developed by D’Aspremont and Jacquemin (1988) to obtain a relationship between the firms’ own R&D cost and level of Jacobian R&D spillovers that will affect firms’ location choice. Our results suggest policy makers should consider the cost of R&D and the R&D spillovers before deciding which industries to be encouraged to form an industrial zone. When the cost of R&D is below a threshold level, it is better for the firms from different industries to agglomerate. However, when the cost of R&D reaches above the threshold level, the firm has to consider the level of Jacobian spillovers that could occur. Only when the spillover effect is below a certain benchmark, it is more profitable for the firms to locate near each other.